Novel methodology to quantify dehydration in head and neck cancer radiotherapy using DIXON MRI. Issue 4 (28th June 2022) - Duncan, Sophie; Walker, Amy; Kumar, Shivani; Dundas, Kylie; Bell, Katherine; Wallis, Andrew; Surjan, Yolanda; Aly, Farhannah; Lee, Mark
Abstract: Introduction: Head and neck cancer (HNC) patients are at risk of weight change, due to inadequate nutrition intake or dehydration, when receiving radiotherapy (RT). This study aimed to develop methodology to measure water content changes on magnetic resonance imaging (MRI) scans of the head and neck region over the course of RT. Methods: Retrospective datasets of 54 patients were analysed. Eligible patients had been treated for HNC with cisplatin chemoradiation (CRT) or RT alone and underwent a minimum of 2 MRI scans from weeks 0, 3 and 6 of their treatment. Anatomical regions consisting of ≥90% water, on T2‐weighted DIXON MRI sequences, were contoured. Water volume changes of all patients were evaluated, within an anatomically standardised external volume, by comparing the absolute water fraction volume (cc) (VEx90WF) and relative water fraction volume (%) (RelVEx90WF) at weeks 0 and 6 of RT. Results: There was a statistically significant difference between the RelVEx90WF at weeks 0 and 6 ( P = 0.005). However, no statistically significant difference was identified between weeks 0 and 6 VEx90WF ( P = 0.064). There were no statistically significant differences identified between patients who received CRT versus RT alone. Conclusion: This study developed a novel method for measuring changes in water fraction volumes over time, using T2‐weighted DIXON MRIs. The methodology created in this study requires further validation through phantom imaging, with known fat and water values. Abstract : Head and neck cancer (HNC) patients are at risk of weight change, due to inadequate nutrition intake or dehydration, when receiving radiotherapy (RT). 4 This study aimed to develop methodology to measure water content changes on magnetic resonance imaging (MRI) scans of the head and neck region over the course of RT.